STRATEGI SISTEM PENGENDALIAN INTERNAL PIUTANG PADA KANTOR PUSAT KSP BALO’TA TANA TORAJA - Maria Amaral Lambe (AJAR, 2020)
Good accounts receivable control will affect the company's success in carrying out the sales policy on credit. Credit sales have a risk that is the existence of bad debts that can cause losses to the company. The object of research is KSP Balo’ta in Toraja. The purpose of this research is to optimize the management of accounts receivable and find new strategies in order to increase the level of effectiveness of the credit control system at Ksp Balo’ta in Toraja. The approach used in this research is qualitative approach and the method used is descriptive method. The results showed that the internal control system of receivables is still less effective it is seen in the increase in problem receivables from year to year. The conclusion of this research is that the receivables control system which is done with a family approach does indeed provide good results, but requires a long process in paying off bad debts. Therefore it is very important for companies to conduct evaluations in order to optimize their receivables management with a new receivables control strategy.